Eksplorasi Etnomatematika pada Permainan Tradisional Congklak di Kelurahan Srengseng Sawah - Sopie Halimah; Aziza Fajriah; Vaniatul Lativa; Ema Lestari; Friska Agustina Silaban (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Ethnomathematics contributes greatly to the improvement of mathematics learning, because it relates to students' experiences in everyday life that touches the realm of local cultural arts so that students become more understanding of the mathematical concepts explained. This study aims to explore the concept of mathematics in the traditional game of congklak in Srengseng Sawah Village. This research is a qualitative research with an ethnographic approach. The data collection techniques used are observation, interview and documentation. The instruments in this study were researchers, observation guidelines, interview guidelines and documentation. Based on the research analysis and discussion of the history and philosophy of the traditional game of congklak, mathematical concepts in the game of congklak such as the concept of flat shapes, namely semicircles, circles, rectangles and spatial shapes, namely half a ball; the concept of transformation in this case reflection / mirroring; the concept of arithmetic calculation operations including addition, subtraction, multiplication and division. The game also has cultural and philosophical values.